2017
DOI: 10.1088/1361-6641/aa6778
|View full text |Cite
|
Sign up to set email alerts
|

Band structure engineering strategies of metal oxide semiconductor nanowires and related nanostructures: A review

Abstract: The electronic band structure of a solid state semiconductor determines many of its physical and chemical characteristics such as electrical, optical, physicochemical, and catalytic activity. Alteration or modification of the band structure could lead to significant changes in these physical and chemical characteristics, therefore we introduce new mechanisms of creating novel solid state materials with interesting properties. Over the past three decades, research on band structure engineering has allowed devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 109 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…Before heat treatment the lattice spacing was found to be 0.28 nm for ZnO, however, after heat treatment the lattice spacing was 0.32 nm based on HRTEM image. Literature data confirmed that both values belong to different facets ((0001) and (0110)) of a regular wurtzite hexagonal-structure ZnO particle [61,62]. It was also detected that the particles directly on the surface showed lower crystallinity compared to other quasi separated crystals.…”
Section: Resultsmentioning
confidence: 80%
“…Before heat treatment the lattice spacing was found to be 0.28 nm for ZnO, however, after heat treatment the lattice spacing was 0.32 nm based on HRTEM image. Literature data confirmed that both values belong to different facets ((0001) and (0110)) of a regular wurtzite hexagonal-structure ZnO particle [61,62]. It was also detected that the particles directly on the surface showed lower crystallinity compared to other quasi separated crystals.…”
Section: Resultsmentioning
confidence: 80%
“…The placement of redox potential with respect to the semiconductor conduction and valence band (VB) energy levels has also become important in order to sustain a specific photocatalytic reaction. Therefore, band-gap re-engineering through doping, noble metal loading, or dye sensitization has become a practical requirement for enhancing the photocatalytic activity of a material. However, such specialized treatment may seriously limit mass-scale production of the material given the high cost of production. , Alternatively, semiconductors with a narrower band gap, for example, Cu 2 O, which is one of the best metal oxides suited for terrestrial photocatalytic applications, have become attractive given the materials’ earth abundance, nontoxicity, and compatibility with a variety of cost-effective scalable fabrication techniques. , Similar photocatalytic metal oxides have since been reported and used in a variety of important photoelectrochemical reactions: for example, reduction of CO 2 in the presence of water, degradation of organic pollutants in air or aqueous media, and removing heavy metals from water. ,, Synthesis of nanostructured photocatalytic materials has also attracted great attention due to the remarkable enhancement of physical and chemical properties when compared to their bulk counterpart. The increase in the surface-to-volume ratio by nanostructuring not only enables harvesting of more photons, resulting in more photoinduced electron–hole pairs, but also its nanoscale surface morphology offers shorter charge transport pathways and more redox active sites, leading to increased reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide semiconductors, including TiO 2 , NiO, SnO 2 , WO 3 , ZnO, Fe 2 O 3 , CuO, and V 2 O 5 , are important ingredients for various energy devices due to their desired electronic and optical properties . The stoichiometry in the metal oxides may vary depending on the synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%